2021
DOI: 10.1186/s12935-021-02109-1
|View full text |Cite
|
Sign up to set email alerts
|

WD40 repeat 43 mediates cell survival, proliferation, migration and invasion via vimentin in colorectal cancer

Abstract: Background WD40 repeat (WDR)43 is an RNA-binding protein that belongs to the WDR domain protein family. Its biological function is largely unclear, particularly in colorectal cancer (CRC). Methods In the present study, we searched the TCGA database and found the correlation between WDR43 and CRC. Subsequently, the high expression of WDR43 in human clinical samples of CRC was validated and we further examined the biological functions of it in CRC ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…NOTUM, one of the Wnt target genes, was found to be up-regulated in clinical specimens of colon cancer 40 . Similarly, immunohistochemistry detection confirmed WDR43 overexpression in CRC patient specimens 41 . What’s more, several studies have reported the oncogenic role of TRIB3 in CRC 42 .…”
Section: Discussionmentioning
confidence: 61%
“…NOTUM, one of the Wnt target genes, was found to be up-regulated in clinical specimens of colon cancer 40 . Similarly, immunohistochemistry detection confirmed WDR43 overexpression in CRC patient specimens 41 . What’s more, several studies have reported the oncogenic role of TRIB3 in CRC 42 .…”
Section: Discussionmentioning
confidence: 61%
“…Dysregulation of protein synthesis and degradation pathways, including the ubiquitin-proteasome system and autophagy-lysosome pathway, has been implicated in the pathogenesis of PD, and previous research has suggested that WDR43 may play a role in ribosome biogenesis and protein synthesis. In addition, WDR43 has been implicated in the development of human estrogen receptor-negative breast cancer and identified as a possible therapeutic target for colorectal cancer ( Couch et al, 2016 ; Bi et al, 2019 ; Li et al, 2021 ; Sun et al, 2022 ). Furthermore, WDR43 and NOL11 are required to form a protein complex to ensure successful segregation of chromosomes at kinetochores and centromeres ( Shibamura et al, 2004 ; Fujimura et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, several bioinformatics analysis identified WDR43 as a crucial oncogene contributing to the development of colorectal/lung cancer via promoting the migration and proliferation of cancer cells through GEO and The Cancer Genome Atlas (TCGA) database. Mechanistically, c-MYC/WDR43/MDM2 mediated p53 degradation, and cyclin-dependent kinase 2 were involved in the underlyng mechanism [ 34 36 ]. However, the role of WDR43 in PAH remains uninvestigated..…”
Section: Discussionmentioning
confidence: 99%